Reelin protects against amyloid β toxicity in vivo - Lane-Donovan, Courtney (Sci Signal, 2015)
Alzheimer's disease (AD) is a currently incurable neurodegenerative disorder and the most common form of dementia in people over the age of 65. The predominant genetic risk factor for AD is the ε4 allele encoding apolipoprotein E (ApoE4). The secreted glycoprotein Reelin, which is a physiological ligand for the multifunctional ApoE receptors Apolipoprotein E receptor 2 (Apoer2) and very low-density lipoprotein receptor (Vldlr), enhances synaptic plasticity. We have previously shown that the presence of ApoE4 renders neurons unresponsive to Reelin by impairing the recycling of the receptors, thereby decreasing its protective effects against amyloid β (Aβ) oligomer-induced synaptic toxicity in vitro. Here, we show that when Reelin was knocked out in adult mice, these mice behaved normally without overt learning or memory deficits. However, they were strikingly sensitive to amyloid-induced synaptic suppression, and had profound memory and learning disabilities at very low amounts of amyloid deposition. Our findings highlight the physiological importance of Reelin in protecting the brain against Aβ-induced synaptic dysfunction and memory impairment.